2020
DOI: 10.1002/ps.6179
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a combined insecticide–rodenticide product on ectoparasite and commensal rodent mortality

Abstract: BACKGROUND Ectoparasites may transfer zoonotic pathogens from rodents to humans or livestock when rodents are managed with rodenticides. This could be minimized using a product combining a rodenticide with a delayed action and a systemic insecticide/acaricide that rapidly kills ectoparasites. Such a combination was tested in commensal pest rodent species to assess efficacy and timing of responses in rodents, and fleas and ticks feeding on them. Ticks or fleas attached to rats (Rattus norvegicus) and house mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…4 In addition to causing high mortality in rodents, it increases the loads of flea or tick on the surviving population of rodents. 5 Previous studies indicated that fleas could survive for 5-15 days without sucking blood from hosts. 6 Therefore, it is necessary to develop a novel method that can provide synergistic control of rodents and vectors of diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In addition to causing high mortality in rodents, it increases the loads of flea or tick on the surviving population of rodents. 5 Previous studies indicated that fleas could survive for 5-15 days without sucking blood from hosts. 6 Therefore, it is necessary to develop a novel method that can provide synergistic control of rodents and vectors of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional culling of rodents with rodenticides has been widely used to reduce their number, but it often suffers from various setbacks such as rapid population recovery after poisoning, high risk to non‐target animals and are against some people's beliefs 4 . In addition to causing high mortality in rodents, it increases the loads of flea or tick on the surviving population of rodents 5 . Previous studies indicated that fleas could survive for 5–15 days without sucking blood from hosts 6 .…”
Section: Introductionmentioning
confidence: 99%
“…2001; Rust 2020; Hinds et al. 2021). A recent study indicated that baits containing 0.001% fipronil killed more than 90% of stickfast fleas ( Echidnophaga gallinacea ) and cat fleas ( Ctenocephalides felis ) on Norway rats (Jacob et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to kill fleas and ticks before killing rodents to minimize the spillover risk after rodent control (Leirs et al 2001;Hinds et al 2021). Adding insecticides into the baits of rodenticides has been proposed to control both rodents and ectoparasites (Leirs et al 2001;Rust 2020;Hinds et al 2021). For example, fipronil and imidacloprid are effective in killing fleas after oral intake by animals (Leirs et al 2001;Hinds et al 2021;Jacob et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation